A systematic review of behavioural techniques used in nutrition and weight loss interventions among adults with mobility‐impairing neurological and musculoskeletal conditions. Issue 12 (30th September 2014) - Plow, M. A.; Moore, S.; Husni, M. Elaine; Kirwan, J. P.
Summary Obesity is a common comorbidity in adults with mobility‐impairing neurological and musculoskeletal conditions, such as stroke and arthritis. The interaction between mobility impairments and environmental factors often compromises motivation and ability to engage in healthy behaviours. Such difficulties to engage in healthy behaviours can result in energy imbalance, weight gain and a cycle of functional declines; i.e. obesity can exacerbate mobility impairments and symptoms and increase the likelihood of other comorbid conditions, all of which make it more difficult to engage in healthy behaviours. To help disrupt this cycle, there is a need to identify strategies to optimize energy balance. Thus, this review summarizes clinical trials of nutrition and weight loss interventions in adults with mobility‐impairing conditions. Although adults with osteoarthritis were represented in large rigorous clinical trials, adults with neurological conditions were typically represented in studies characterized by a small number of participants, a short‐term follow‐up and high attrition rates. Studies varied greatly in outcome measures, description and implementation of the interventions, and the strategies used to promote behaviour change. Nutrition and weight loss research in adults with mobility‐impairing conditions is still in its formative stages, and there is a substantial need to conduct randomized controlled trials.